Determinantes da estrutura de capital de sociedades anônimas mineiras de capital fechado - Danillo Lemes Gonçalves (2014)
This study had the objective of verifying which are the determinants factors of the capital structure of closed capital business corporations. For over half a century work of this nature are developed by researchers in finance, however, it is observed that the majority of the studies use open capital companies operating in the stock market due to the easy access to their data. This study sought to determine whether the relationships found in the literature are also significant among the determinants factors and the capital structures of closed capital business corporations. To this end, a survey of data in the financial statements (2009-2012) of 62 private mining companies that have reported their financial information on the Journal Diário do Comércio de Minas Gerais was performed. Through a multiple regression with unbalanced panel data, the study included 204 observations to verify how the factors profitability, taxes and contributions, degree of immobilization, size and growth behave on the levels of total debt, on the short and long term of the companies analyzed. The results suggest that profitability, size and growth are significant factors in explaining the levels of total and short-term debts, and that the degree of immobilization has explanatory power to explain the long-term debt of closed capital mining corporations. The relationships found for the factors profitability, growth and degree of immobilization are coherent with the Pecking Order Theory. The findings also suggest that the closed capital business corporations prefer to fund their capital necessities with internally generated funds, and only on the insufficiency of these funds would they resort to debt. The size factor showed a positive relationship with total and short-term debt, suggesting that larger companies have greater tendency to get loans, as foreseen by the Agency Theory and the Costs of Bankruptcy. These evidences suggests that the determinants factors of open capital companies are also statistically significant in explaining the capital structures of closed capital business corporations, as well as that the major theories of capital structure are consistent to explain the evidence found, being recommended that further research be developed with larger and more representative samples so that the results can be generalized.